Analyzing economic policies that affect supply and demand: a structural model of productivity, labor supply and rationing - Kai-Uwe Müller (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper a labor supply model with demand side rationing is estimated to analyze the economic policies that directly affect incentives to work as well as labor costs. The framework is applied to evaluate the employment effects of a federal minimum wage in Germany and the impact of employer- vs. employee-oriented wage subsidies under a statutory minimum. We extend Laroque and Salani (2002) by modeling the extensive and intensive margin of labor supply on the basis of desired working hours. While previous studies for Germany Bargain et al. (2010) identify the rationing risk primarily from exogenous demand side factors, this paper structurally relates it to individual productivity which is determined in a jointly estimated wage/productivity equation. Unobserved individual factors are allowed to influence preferences and constraints. The variation needed to identify labor supply and demand is generated by the tax and transfer system and labor market regulations defining minimum standards of pay. Simulation exercises prove the value of the model for policy analysis. Differing adjustments at the extensive and intensive margin are revealed that are related to heterogeneous productivities.
Keywords: J23; J31; J22; 330